Corporate Governance and Innovation: Theory and Evidence. (23rd January 2015) - Sapra, Haresh; Subramanian, Ajay; Subramanian, Krishnamurthy V.
Abstract We develop a theory to show how external and internal corporate governance mechanisms affect innovation. We predict a U-shaped relation between innovation and external takeover pressure, which arises from the interaction between expected takeover premia and private benefits of control. Using ex ante and ex post innovation measures, we find strong empirical support for the predicted relation. We exploit the variation in takeover pressure created by the passage of antitakeover laws across different states. Innovation is fostered either by an unhindered market for corporate control or by antitakeover laws that are severe enough to effectively deter takeovers.